Genome-wide analysis of gene regulation mechanisms during Drosophila spermatogenesis - Laktionov, Petr P. (Epigenetics Chromatin, 2018)
BACKGROUND: During Drosophila spermatogenesis, testis-specific meiotic arrest complex (tMAC) and testis-specific TBP-associated factors (tTAF) contribute to activation of hundreds of genes required for meiosis and spermiogenesis. Intriguingly, tMAC is paralogous to the broadly expressed complex Myb-MuvB (MMB)/dREAM and Mip40 protein is shared by both complexes. tMAC acts as a gene activator in spermatocytes, while MMB/dREAM was shown to repress gene activity in many cell types. RESULTS: Our study addresses the intricate interplay between tMAC, tTAF, and MMB/dREAM during spermatogenesis. We used cell type-specific DamID to build the DNA-binding profiles of Cookie monster (tMAC), Cannonball (tTAF), and Mip40 (MMB/dREAM and tMAC) proteins in male germline cells. Incorporating the whole transcriptome analysis, we characterized the regulatory effects of these proteins and identified their gene targets. This analysis revealed that tTAFs complex is involved in activation of achi, vis, and topi meiosis arrest genes, implying that tTAFs may indirectly contribute to the regulation of Achi, Vis, and Topi targets. To understand the relationship between tMAC and MMB/dREAM, we performed Mip40 DamID in tTAF- and tMAC-deficient mutants demonstrating meiosis arrest phenotype. DamID profiles of Mip40 were highly dynamic across the stages of spermatogenesis and demonstrated a strong dependence on tMAC in spermatocytes. Integrative analysis of our data indicated that MMB/dREAM represses genes that are not expressed in spermatogenesis, whereas tMAC recruits Mip40 for subsequent gene activation in spermatocytes. CONCLUSIONS: Discovered interdependencies allow to formulate a renewed model for tMAC and tTAFs action in Drosophila spermatogenesis demonstrating how tissue-specific genes are regulated. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13072-018-0183-3) contains supplementary material, which is available to authorized users.